PENERAPAN MODEL TEAMS GAMES TOURNAMENT (TGT) BERBASIS PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) TERHADAP MINAT BELAJAR PESERTA DIDIK - Salsa Ulwiyah Ulfiyana; Sari Yustiana; Muhamad Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In Indonesian subjects, the conventional learning model is still used by teachers, the source of material used is limited to LKS books that are not relevant to the background and culture of students, so that this is the reason for the lack of interest in learning students. The purpose of this study is to identify students learning interests using the application of the Teams Games Tournament (TGT) model based on the Culturally Responsive Teaching (CRT) approach. This type of research uses quantitative descriptive. The research was carried out at SD N Kalisari 1 in November 2024. The sample used was all class VI students totaling 36 students. Techniques in collecting data using questionnaires. The results of the study showed that students who had a high interest in learning reached a percentage of 58.33%, the medium interest criterion was 41.66%, and the low criterion was 0%. The average percentage of students interest in learning showed high criteria with a result of 76.02%. It can be concluded that the application of the Teams Games Tournament (TGT) model based on the Culturally Responsive Teaching (CRT) approach can increase students interest in learning Indonesian subjects.